Effects of application of groundnut biomass compost on uptake of phosphorus by maize grown on an Ultisol of South Sulawesi - K Kasifah; S Syekhfani; Y Nuraini; E Handayanto (Journal of Degraded and Mining Lands Management, 2014)
Low crop production is acid dryland area of South Sulawesi is due to low availability of P in the soils. One of alternatives that can be performed to overcome the problems of acid soils having high level of exchangeable Al, is through the addition of organic material. In the upland areas in South Sulawesi, crop rice, maize and groundnut crop residues are readily available, but the crop residues are generally only used as animal feed or even burned. This study was aimed to elucidate the effects of groundnut compost on P uptake by maize in Ultisol of Moncongloe, South Sulawesi. Eight kilograms of air dried soil was mixed with compost according to the following treatments; 0, 10, 15, 20, 25, 30, 35 and 40 t compost/ha. All pots received 200 kg/ha KCl and 300 kg Urea/ha as basal fertilizers. Two maize seeds were planted in each pot and thinned to one plant per pot after one week. At harvest maize shoot dry weight and maize root dry weight, length of maize cop, cob weight, cob diameter, weight grains per cob, P uptake by maize, P content in maize grain, soil available P were measured. Results of the study showed that groundnut compost has the ability to improve the availability of P in the soil and increase P uptake by maize grown on an Ultisol of South Sulawesi. Application of 25 t groundnut compost/ha was the optimal rate that can be used to increase P availability in an Ultisol of South Sulawesi.